Income smoothing and firm value in a regulated market: the moderating effect of market risk - Segun Abogun; Ezekiel Aiyenijo Adigbole; Titilope Esther Olorede (Asian Journal of Accounting Research, 2021)
This study aims to examine the impact of income smoothing on the value of firms in a regulated security market, moderated by market risk. This is based on the prevalence of accounting scandals resulting in the collapse of firms which has been attributed to the opportunistic behaviors of managers.The ex post facto research design was employed, and as such, data were gathered from secondary sources. The quantitative approach was also used in the study. Furthermore, the system generalized method of moments (Blundell–Bond) panel estimation technique was used for analyzing the data. Income smoothing was measured using the accrual based methods, while firm value was measured using share price.The study found that income smoothing has a negative significant impact on firm value. The study also revealed that market risk is a significant variable that defines the relationship between income smoothing and firm value.Testing the moderating effect of market risk on the relationship between income smoothing and firm value is unique to this study, particularly from a regulated security market and emerging economy.